Measurement of prompt D0, D+, D*+, and D+S production in p-Pb collisions at √sNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; Ohlson, Alice; et al. (Journal of high energy physics, 2019)
The measurement of the production of prompt D0, D+, D*+, and D+S mesons in proton–lead (p–Pb) collisions at the centre-of-mass energy per nucleon pair of √sNN = 5.02 TeV, with an integrated luminosity of 292 ± 11 μb−1, are reported.